Reactions and Plans of the State Leadership of Serbia and Montenegro during the Crisis in Kosovo and Metohija (March 17–19, 2004) - Dimitrijević, Nemanja S. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
The article analyzes the reactions and plans of the state leadership of Serbia and Montenegro during the crisis in Kosovo and Metohija in March 17‒19, 2004, when radicalized groups of Kosovo Albanians expelled more than 4,000 Serbs from their homes. The same radicalized groups burned and destroyed 35 churches of the Serbian Orthodox Church. The state leadership of Serbia and Montenegro monitored the situation in Kosovo and Metohija and was ready to engage the army with the task of creating the humanitarian corridor for the evacuation of Serbs from Kosovo and Metohija to Serbia. During the crisis, the state leadership of Serbia and Montenegro did not send the army to Kosovo and Metohija because KFOR units stopped the expulsion of Serbs and the destruction of the cultural heritage of Serbian people.
Keywords: Kosovo and Metohija; March pogrom; humanitarian corridor; Boris Tadić; Nebojša Čović; 2004